A Cost Comparison of Holmium Laser Enucleation of the Prostate with and without Moses™. Issue 6 (16th November 2021) - Lee, Matthew S.; Assmus, Mark; Agarwal, Deepak; Large, Tim; Krambeck, Amy
Abstract: Introduction: Holmium laser enucleation of the prostate (HoLEP) is a size-independent treatment option for the treatment of benign prostatic hyperplasia. HoLEP has been shown to have excellent improvements in prostate symptom scores and maximum flow rates that have been durable for 2 decades. However, the steep learning curve associated with HoLEP has prevented its widespread adoption. New advancements in lasers, specifically the Moses™ pulse-modulation technology, have resulted in improvements in hemostasis and achieving same-day discharges and catheter removals. We aimed to perform a cost-comparison to analyze if Moses-augmented HoLEP (m-HoLEP) resulted in cost-savings. Methods: A retrospective review was performed of a single expert surgeon's experience from May 2018 to November 2020, comparing m-HoLEP with HoLEP. Perioperative and postoperative variables were abstracted from the medical record. Univariate and multivariate analyses were performed using SAS® 9.4. Two-sided significance was set at p <0.05. Results: A total of 312 men underwent HoLEP during the study period (192 in m-HoLEP group and 120 in HoLEP group). The m-HoLEP group had more same-day discharges (p <0.001) and emergency department visits (6.3% vs 1.7%, p=0.0071). m-HoLEP resulted in hospital cost savings of $840 for the initial surgical episode (p=0.0297). When factoring in emergency department visits/readmissions, the cost savings decreased to $747 per case (p=0.0574). Conclusions: m-HoLEP was associated with same-day discharge and hospital cost savings of $840 for the initial surgical episode. Further study in other institutions with surgeons of varying experience levels will need to be performed to see if these findings can be replicated.